Identification of powdery mildew resistance quantitative trait loci in melon and development of resistant near-isogenic lines through marker-assisted backcrossing - Chun-San Wang; Ssu-Yu Lin; Jin-Hsing Huang; Hsin-Yi Chang; Di-Kuan Lew; Yu-Hua Wang; Kae-Kang Hwu; Yung-Fen Huang (Botanical Studies)
Abstract Background Melon (Cucumis melo L.), an important cucurbit crop, faces production limitations due to powdery mildew (PM). Developing resistant varieties offers a sustainable, genetics-based alternative to chemical treatments. Therefore, identifying PM resistance quantitative trait loci (QTL) and creating trait-associated markers are essential for efficient melon PM resistance improvement through marker-assisted backcrossing (MABC). Results Three F2 populations, A6, B2, and C4, were generated for QTL mapping of PM resistance. Major QTL were identified on chromosome 2 in A6, chromosome 5 in B2, and chromosomes 5 and 12 in C4. A series of TaqMan® assays targeting regions on chromosomes 2, 5, and 12 were developed and validated for foreground and recombinant selection, complemented by the double digest restriction-site associated DNA genotyping system to evaluate the recurrent parent genome recovery. Three MABC programs using resistant donor parents from A6 and C4 crossed with elite susceptible recurrent parents with green and orange fruit flesh were implemented. After two to three cycles of MABC, individual QTL was successfully introgressed into elite genetic backgrounds, giving six PM resistance lines in each green- and orange-fleshed background. PM inoculation on the twelve near-isogenic lines confirmed their resistance to PM. Conclusions We have identified major PM resistance QTL for melon on chromosomes 2, 5, and 12 and have introgressed individual QTL to elite genetic backgrounds using MABC in three and a half years. This study demonstrates the power of combining high-throughput genotyping with breeding efforts and showcases the efficiency of molecular breeding.